2020
DOI: 10.1007/s10592-020-01268-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of regional water vole populations and footprints of reintroductions: a case study from southeast England

Abstract: An important consideration when implementing species management is preserving genetic variation, which is fundamental to the long-term persistence of populations and adaptive potential of the species. The European water vole Arvicola amphibius is of high conservation importance in the United Kingdom due to its documented decline in both distribution and abundance. Conservation strategies for this species include protecting source populations, increasing habitat availability and connectivity, non-native predato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The maintenance of these two British lineages is necessary due to their considerable divergence and their distinct evolutionary history. In the Southeast of England, water vole mtDNA was found to be structured by watershed and it was suggested that conservation management should take place at a local level to maintain local genetic heritage [ 13 ]. Ex-situ conservation can be a useful tool to halt the decline of species, especially when genetics and pedigrees are considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance of these two British lineages is necessary due to their considerable divergence and their distinct evolutionary history. In the Southeast of England, water vole mtDNA was found to be structured by watershed and it was suggested that conservation management should take place at a local level to maintain local genetic heritage [ 13 ]. Ex-situ conservation can be a useful tool to halt the decline of species, especially when genetics and pedigrees are considered.…”
Section: Discussionmentioning
confidence: 99%
“…In the Southeast and East of England populations of natural water voles showed considerable haplotype diversity and substantial genetic structure between watershed populations, and finer-scale structure between populations within watersheds, when using the mitochondrial DNA control region and microsatellite markers of natural populations [ 13 , 14 ]. However, a detailed study on captive populations of water voles is missing, hindering the outcomes of current conservation efforts.…”
Section: Introductionmentioning
confidence: 99%